The Non-Observance of Gricean Maxims in the Movie Series "Sherlock Holmes" - Najih Suraya (Lexicon, 2012)
This research attempts to investigate the non-observance of Gricean maxims in the movie series Sherlock Holmes. In particular, it attempts to identify and classify the flouting of the maxims found in the movie. The data used in this research are dialogues containing expressions of the non-observance of Gricean maxims. Based on the data analysis, 75 cases of the flouting of Gricean maxims were found: 20 (26.6 %) cases showed the flouting of the quality maxim, 8 (10.6%) the flouting of the quantity maxim, 17 (22.6%) the flouting of the relevance maxim, 20 (26.6 %) the flouting of the manner maxim, and 10 (13.3%) the flouting of a combination of maxims. It was found in this research that the flouting of the quality maxim and the flouting of the manner maxim are considered as most commonly used strategies in the movie.